Design and Construction of an Automation Tool for Feeding Pokdakan Pesawaran Fish - Saputra, Ricco Herdiyan; Hendrawan, Eko (International Journal of Electronics and Communications Systems, 2023)
This study focuses on developing an automated feeding tool for fish farming in Pesawaran, a region known for its aquaculture potential. Aquaculture, crucial for global food needs, requires efficient and sustainable management, especially in feeding, a critical factor in fish growth and health. Traditional manual feeding methods are time-consuming and prone to errors, affecting fish productivity and growth. The research aimed to enhance feed management efficiency, minimize feeding errors, and improve the sustainability and productivity of fish farming in Pesawaran. The initial phase involved analyzing the needs of fish farmers, environmental factors, and fish species. The design of the automation tool emphasized ergonomics, reliability, and ease of use. The Rapid Application Development (RAD) method was employed, focusing on quick and iterative development. This method was applied at the Pokdakan Pemuda Tani RPL in Negeri Sakti Village, Gedong Tataan District, Pesawaran Regency, from July to November 2023. The application of RAD in designing the Pokdakan Pesawaran fish-feeding automation tool yielded positive outcomes. The fast, responsive development process, which actively involved users, led to a practical solution well-received by the fish farming community. This research demonstrates the value of RAD principles in providing practical, locally relevant solutions and guiding the development of adaptive, user-oriented aquaculture technology.